2017
DOI: 10.1007/s12539-017-0251-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Microsatellites in Alternaria arborescens and Elucidation of the Function of Polyketide Synthase (PksJ)

Abstract: Microsatellites or simple sequence repeats (SSRs) have been the most widely applied class of molecular markers used in genetic studies, having applications in genetic conservation, population studies, as well as diagnostics of fungi. Mining and analysis of SSRs of the whole genome sequence have been carried out in this study for the fungus Alternaria arborescens causing early blight of tomato and well known for producing mycotoxins like alternariol (AOH), alternariol monomethyl ether (AME), etc. A total of 409… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, the current study was performed on the complete genome assembly of Uh4857-4 and Uh364 isolates and non-coding sequences were also included. As a consequence, it permits to report a huge number of microsatellites (100239 in Uh364 and 137442 in Uh4857-4) compared to earlier reports in phytopathogenic fungi (Kumar et al, 2012;Singh et al, 2014a;Zhang et al, 2015;Mahfooz et al, 2017;Choudhary et al, 2018;Varady et al, 2018). In the present study, the relative abundance of microsatellites in the whole genome of Uh4857-4 (5246.27 microsatellites per Mb) and Uh364 (5125.14 microsatellites per Mb) is quite similar, suggesting the highly homogeneous genomic structure of these two U. hordei isolates.…”
Section: Discussionmentioning
confidence: 87%
“…However, the current study was performed on the complete genome assembly of Uh4857-4 and Uh364 isolates and non-coding sequences were also included. As a consequence, it permits to report a huge number of microsatellites (100239 in Uh364 and 137442 in Uh4857-4) compared to earlier reports in phytopathogenic fungi (Kumar et al, 2012;Singh et al, 2014a;Zhang et al, 2015;Mahfooz et al, 2017;Choudhary et al, 2018;Varady et al, 2018). In the present study, the relative abundance of microsatellites in the whole genome of Uh4857-4 (5246.27 microsatellites per Mb) and Uh364 (5125.14 microsatellites per Mb) is quite similar, suggesting the highly homogeneous genomic structure of these two U. hordei isolates.…”
Section: Discussionmentioning
confidence: 87%
“…Fleck et al [47] reported that AOH-induced reactive catechols react covalently with DNA forming depurinating adducts at the N-7 of guanine and the N-3 of adenine. Tiessen et al [48] added that AOH exposure induced complex distributions of γH2AX histones which are paramount biomarkers of DNA double strand breaks (DSBs) and strong indicator that AOH-induced DSBs are important triggering signals for G2 arrest and autophagy [49]. AOH has been proved as a DNA topoisomerase poison with certain selectivity for its IIa isoform [50].…”
Section: Discussionmentioning
confidence: 99%
“…These methods also lack precision and accuracy. There are a flood of research reports that illustrate the potential of nucleic acid-derived markers for unzipping the variation among fungal pathogens at the genome level ( Kumar et al, 2013 ; Kashyap et al, 2015 , 2019b ; Goswami et al, 2017 ; Choudhary et al, 2018 ; Jiménez-Becerril et al, 2018 ; Prasad et al, 2018 ). For instance, genetic markers such as inter simple sequence repeats (ISSR) and random amplified polymorphic DNA (RAPD) have been extensively utilized to understand the genetic diversity of T. indica isolates ( Avinash et al, 2000 ; Seneviratne et al, 2009 ; Aggarwal et al, 2010 ; Parveen et al, 2015 ; Aasma et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%